The Impact of Eco Enzymes on Generative and Vegetative Development in Various Mutant Lines of Kipas Merah Soybean (Glycine max (L) Merr.) - Zuyasna Zuyasna; Nura Nura; Meutia Maharani; Farida Iriani (Ann Publisher, 2025)
Background. A native Acehnese soybean variety that is suited to the Aceh agroecosystem is the Kipas Merah variety. By creating drainage ditches to prevent flooding during rainy seasons, Var. Kipas Merah can be planted in rice fields either after the rice harvest or at the end of the rainy season, utilizing a no-till planting technique. Aims. The research aims to find the effect of eco enzyme application on several 7th-generation Kipas Merah soybean mutant lines on vegetative and generative growth. Methods. From April to October 2023, the study will be conducted in the experimental garden of Syiah Kuala University's Faculty of Agriculture. A randomized full block design with three replications and a 3 x 4 factorial pattern was employed in the investigation. The three levels of eco enzyme (K) concentration (K0, K1, and K2) as well as the genotype of Kipas Merah mutant soybeans (Kipas Merah, A1, A7, and A11) were the factors under investigation. Result. The findings demonstrated that the Kipas Merah soybean variety significantly impacted plant height and that the concentration of 10 ml L-1 was superior to other treatments. However, the A11 mutant produced superior outcomes. Conclusion. The combination of eco enzyme concentration and mutant lines with better values was found in 10 ml L-1 and A11.